Implementasi Perlindungan Hukum Dan Penyelesaian Perselisihan Transaksi Fraud Bagi Pemegang Kartu Kredit - Hasmonel Hasmonel (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
The aim of this research is to discover, analyze and examine the practice/ implementation of legal protection for credit card holders and forms of consumer protection in resolving fraudulent transaction disputes. The research method used in this research is normative juridical using a qualitative approach. Apart from that, a literature approach and a statutory approach are also used which also include a conceptual approach and a case approach. Credit cards are a form of innovation in the banking business which is increasingly developing and banking transactions using credit cards are becoming more massive. However, if negligence or fraud occurs, the bank's position is very dominant which will of course prioritize the bank's own interests. Therefore, currently the position and interests of customers have not been properly protected. The demand for banks to act professionally while protecting their credit card holders is increasing, thus encouraging banks to adjust their efforts to serve their customers, one of which is by creating innovations while remaining efficient. This is clearly seen in the agreement between the bank and the customer or the provisions regarding the use of bank services or products which are determined unilaterally by the bank, so that in such conditions if a problem arises later it cannot be resolved quickly with clear responsibilities. One example is the Indonesian Supreme Court Decision No.1527 K/Pdt/2015. regarding the Bank Mandiri Tbk case. VS Mr Sutrisno. Based on this decision, even though Mr. Sutrisno had obtained legal protection that had permanent legal force and fulfilled a sense of justice, this was done in approximately 3 (three) years, where previously Sutrisno as a credit card holder had been harmed by a Bank Mandiri credit card product that had never been he uses but has a number of obligations that must be paid.